Fostering organisational resilience in print and media industry in Sri Lanka: The role of dynamic capability and strategic orientation - Nuwan, Nalinda (Journal of Print and Media Technology Research, 2024)
Organisational resilience has gained significant prominence as a result of unprecedented shocks in the corporate marketplace,where print and media enterprises are particularly vulnerable. Therefore, print and media enterprises are required to develop organisational resilience strategically, focusing on fostering business resilience. In this context,the theory of dynamic capability offers a framework for print and media enterprise leaders to navigate capabilities toward potential opportunities. This research provides an extensive framework to examine the relationship between organisational resilience and dynamic capability. Primary data were gathered from 300 print and media Enterprise leaders in Sri Lanka using a structured questionnaire. The data was analysed using SPSS and AMOS. The findings indicate that a well-combined set of dynamic capabilities, centered around seizing new opportunities, has a significant effect on improving company resilience in the PME sector. Moreover, strategic orientation plays a significant role as a mediator between dynamic capability and organisational resilience. A key finding of this study further reveals that company characteristics and market conditions also have a considerable effect on fostering organisational resilience.The study suggests that older print and media enterprises must adopt a more strategic orientation and reforms must be implemented to enhance company resilience in the print and media industry in Sri Lanka.